The impact of HR practices on burnout core and secondary symptoms: The mediating roles of trust, optimism role conflict and job insecurity - Sinval, J.; Silva, S. da (Proceedings of the 16th European Academy of Occupational Health Psychology, 2024)
Background: The relevance of HR practices for worker well-being and mental health has been highlighted by several authors (e.g., Guest, 2017; Saks, 2022). Positive outcomes of HR practices may be explained by their impact on workers' attitudes, motivation, basic needs satisfaction, or due to their influence on perceptions of the organizational climate and improvement of labour relations. Although there are already studies supporting this relationship, only two studies have explored its role in burnout (Kroon et al., 2009; Kilroy et al., 2016). In this study, we aim to test whether well-implemented HR practices (i.e., career perspectives; training; participation; performance assessment; information) contribute to trust in the organization, reducing role conflict and job insecurity, and increasing optimism. Through these variables, we expect to observe a positive impact on burnout (reducing burnout).304 Method: We used a cross-sectional design with a sample of workers from a public administration organization. We used a self-report questionnaire to measure the variables of interest. Participants were invited to complete the survey using an online platform. The data were analysed using descriptive statistics and structural equation modelling. Results: Our study collected data from 417 workers, of which 67.4% were aged 40 to 54, and 61.1% held a graduation or post-graduation degree. Most participants were female (73.1%) and professionals (77.5%) according to the ISCO-08 occupational classification. Trust was found to predict burnout core symptoms (? = -0.268; p = .002) and was significantly influenced by career perspectives (? = 0.359; p < .001), participation (? = -0.220; p = .027), performance assessment (? = 0.429; p < .001), and information practices (? = 0.300; p < .001). The indirect effects of trust on burnout core symptoms were statistically significant through career perspectives (? = -0.096; p = .009), performance assessment (? = -0.115; p = .006), and information practices (? = -0.081; p = .008). Role conflict emerged as a predictor of both burnout core (? = 0.307; p < .001) and secondary symptoms (? = 0.269; p < .001), with performance assessment (? = -0.193; p = .006) and information practices (? = -0.314; p < .001) significantly influencing role conflict. The impact of role conflict on burnout core and secondary symptoms was partially mediated by performance assessment (? = -0.059; p = .016) and information practices (? = -0.097; p = .003). Job insecurity, measured qualitatively, was found to predict burnout core (? = 0.447; p < .001) and secondary symptoms (? = 0.262; p < .001). Career perspectives (? = -0.307; p = .010), training (? = 0.155; p < .030), and participation practices (? = -0.441; p < .001) significantly influenced job insecurity. The indirect effects of qualitative job insecurity on burnout core and secondary symptoms were statistically significant through career perspectives (? = -0.137; p = .012), training (? = 0.069; p < .037), and participation practices (? = -0.197; p = .002). The indirect effect of job insecurity on burnout secondary symptoms was statistically significant via career perspectives (? = -0.080; p = .027) and participation practices (? = -0.115; p = .018). Optimism was identified as a predictor of burnout core (? = -0.522; p < .001) and secondary symptoms (? = -0.378; p < .001), with participation (? = 0.342; p = .009) and performance assessment practices (? = 0.269; p < .001) acting as significant predictors. The indirect effects of optimism on burnout core and secondary symptoms were statistically significant via participation (? = -0.179; p = .009) and performance assessment practices (? = -0.140; p < .001). Conclusion: The findings underscore the importance of implementing effective HR practices, such as career perspectives, training, participation, performance assessment, and information sharing, in promoting trust in the organization and reducing role conflict and job insecurity. Additionally, these practices contribute to increased optimism among employees, ultimately leading to reduced burnout. Our results have important implications for both researchers and practitioners in the field of human resource management. For researchers, this study offers a comprehensive understanding of the mechanisms through which HR practices can influence burnout, highlighting the mediating roles of trust in the organization, role conflict, job insecurity, and optimism. Future research could explore additional variables that may play a role in this relationship, such as organizational support, leadership styles, and work-life balance. For practitioners, these findings emphasize the importance of investing in effective HR practices to improve employee well-being and mental health. By focusing on career perspectives, training, participation, performance assessment, and information sharing, organizations can build trust and optimism among their employees, mitigate the negative effects of role conflict and job insecurity, and ultimately reduce the risk of burnout. Future research and practice should continue to explore the role of HR practices in promoting workplace well-being and preventing burnout, as well as identifying additional strategies to support employees in maintaining good mental health.